KONTRIBUSI LPTQ KOTA MEDAN DALAM PENGEMBANGAN MUSABAQAH HADIS PADA AJANG STQH DI SUMATERA UTARA - Hasibuan, Salsabilah; Munandar; Fandi Yulistio; Annisa Nur Fitri; Annisa Billah; Irwansyahputra; Farhah Nabila Damanik (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study stems from observations of the development of hadith competitions, particularly in the city of Medan. The study aims to explore the role of the Medan City LPTQ in the development of Hadith Competitions at the STQH event held in North Sumatra. This study uses a qualitative method with a literature study type. Data was obtained based on a review of literature and websites relevant to the topic of study. The results of the discussion show that the LPTQ hadith plays a significant role in enhancing the development of hadith competitions, as demonstrated by the increasing interest of participants in the hadith category from year to year. In addition, this can be seen through the achievements of the Medan City LPTQ as one of the largest contributors of participants to the STQH event at the national level